Unclean: meditations on purity, hospitality, and mortality - Beck, Richard Allan (Cascade Books, 2011)
"I desire mercy, not sacrifice." Echoing Hosea, Jesus defends his embrace of the "unclean" in the Gospel of Matthew, seeming to privilege the prophetic call to justice over the Levitical pursuit of purity. And yet, as missional faith communities are well aware, the tensions and conflicts between holiness and mercy are not so easily resolved. At every turn, it seems that the psychological pull of purity and holiness tempts the church into practices of social exclusion and a Gnostic "flight" from the world into a "too spiritual" spirituality. In an unprecedented fusion of psychological science and theological scholarship, Richard Beck describes the pernicious (and largely unnoticed) effects of the psychology of purity upon the life and mission of the church